Metode Distributed Practice Pada Phonic Dan Vocabulary Bagi Siswa Usia Dini Di Kecamatan Barus Jahe Tanah Karo - Karisma Erikson Tarigan; Meikardo Samuel Prayuda; Margaret Stevani; Sumarlin Mangandar Marianus (Smart Education, 2022)
Abstract:Matching phonemes (speech sounds) to graphemes (letters and letter combinations) was an important aspect of decoding (translating print to speech) and encoding (translating speech to print). However, most early childhood students did not receive explicit training in correspondence phonemography. Difficulties with accurate phoneme production and lack of understanding of sound symbol correspondences could make it difficult for students to: (1) identify pronunciation errors in general assessments and (2) provide a model of teaching English reading or provide remedial reading instructions. This community service examined the application of the distributed practice method in developing knowledge and phoneme-grapheme correspondence skills for early students. The sample of this study was 35 students aged 7-13 years in the village of semangat barusjahe tanah karo, North Sumatra. The test design consisting of pre-test and post-test was used to compare mass practice conditions (one 60 minute session) with conditionally distributed practice (four 15 minute sessions distributed over 4 weeks) to learn phonemes related to letters and letter combinations. The result of this community service was that students could improve their vocabulary and phonics skills orally and in writing by using English learning. Keyword : distributed practice; phonics and vocabulary; early childhood students Abstrak:Pencocokan fonem (bunyi ucapan) dengan grafem (huruf dan kombinasi huruf) adalah aspek penting dari decoding (menerjemahkan cetak ke ucapan) dan encoding (menerjemahkan ucapan untuk dicetak). Namun, siswa usia dini kebanyakan tidak menerima pelatihan eksplisit dalam fonemografi korespondensi. Kesulitan dengan produksi fonem yang akurat dan kurangnya pemahaman korespondensi simbol bunyi dapat menyulitkan siswa untuk: (1) mengidentifikasi kesalahan pengucapan pada penilaian umum dan (2) memberikan model pengajaran membaca bahasa Inggris. atau memberikan instruksi membaca remedial. Pengabdian kepada masyarakat ini meneliti penerapan metode distributed practice dalam pengembangan pengetahuan dan keterampilan korespondensi fonem-grafeme siswa usia dini. Sampel penelitian ini ialah 35 siswa pelajar usia 7-13 tahun di desa semangat barusjahe tanah karo, Sumatera Utara. Desain tes terdiri dari pre-test dan post-test digunakan untuk membandingkan kondisi latihan massal (satu sesi berdurasi 60 menit) dengan latihan terdistribusi kondisi (empat sesi berdurasi 15 menit yang didistribusikan selama 4 minggu) untuk belajar fonem terkait dengan huruf dan kombinasi huruf. Hasil pengabdian ini ialah siswa dapat meningkatkan keterampilan kosakata dan fonik secara lisan dan tulisan dengan menggunakan pembelajaran bahasa Inggris. Kata Kunci : distributed practice; phonic dan vocabulary; siswa usia dini